Medication reconciliation enhances the accuracy of gastric emptying scintigraphy - Vincent Nail; Alexandre Chapot; Oriane Nachar; Sophie Gabriel; Anaïs Moyon; David Taieb; Benjamin Guillet; Philippe Garrigue (SpringerOpen, 2024)
Abstract Background Gastroparesis (GP) is a prevalent sensorimotor disorder characterized by delayed gastric emptying without mechanical obstruction, posing significant diagnostic challenges. Gastric emptying scintigraphy (GES) is the gold standard for diagnosing GP. However, its accuracy can be compromised by many medications that affect gastric motility. This study evaluates the impact of medication reconciliation on the diagnostic accuracy of GES. Results A significant proportion of patients (75%) were on medications known to affect gastric motility. Recommendations for medication adjustments were communicated, with 30% non-adherence. Adjustments in GES interpretations were necessary for 20% of patients following comprehensive medication reviews. The involvement of radiopharmacists facilitated accurate diagnostic conclusions, underscoring the critical role of medication reconciliation in GES accuracy. Conclusion Medication reconciliation enhanced the accuracy of GES in diagnosing gastroparesis, emphasizing the need to integrate clinical pharmacy practices into nuclear medicine. This interdisciplinary approach not only improves diagnostic accuracy but also enhances patient safety, advocating for the adoption of such practices in the management of gastroparesis.